On protecting data storage in mobile cloud computing paradigm - Abdalla , Al-kindy Athman; Pathan, Al-Sakib Khan (Medknow publication, 2014)
To enhance the security of mobile cloud storage, a few proposals have been presented already, where most of those focus on securing data through passwords and encryption-decryption of data through cryptographic tools and existing or rather new algorithms. However, these passwords and algorithms eventually get cracked by the expert hackers who mostly spend their entire time learning the algorithms and the way to get through the password-protected frameworks. It is with this reason that our paper concentrates on a different way of securing data-storage for the mobile cloud computing users. In this paper, we present a secure framework that helps protect the mobile-user data through storage in different servers located at different geographical locations across the globe. That way, it ensures strong data protection ability, because part of the data is stored in one server located at a location and another part of the data is stored in another server located at a far different location. We also analyze various facets of the issue and report on the state-of-the-art achievements.